Cyclic Lipodepsipeptides From Pseudomonas spp. – Biological Swiss-Army Knives - Geudens, Niels; Martins, José C. (Frontiers in Microbiology, 2018)
Cyclic lipodepsipeptides produced by Pseudomonas spp. (Ps-CLPs) are biosurfactants that constitute a diverse class of versatile bioactive natural compounds with promising application potential. While chemically diverse, they obey a common structural blue-print, allowing the definition of 14 distinct groups with multiple structurally homologous members. In addition to antibacterial and antifungal properties the reported activity profile of Ps-CLPs includes their effect on bacterial motility, biofilm formation, induced defense responses in plants and their insecticidal activity and anti-proliferation effects on human cancer cell-lines. To further validate their status of potential bioactive substances, we assessed the results of 774 biological tests on 51 Ps-CLPs available from literature. From this, a fragmented overview emerges. While Ps-CLPs taken as a group demonstrate a broad activity profile, reports on individual Ps-CLPs mostly test on activities that reflect the scientific focus of the individual authors. The current data is therefore found to be to sparse to correlate structure and biological function. Consequently, generalizations with respect to activity across the Gram-positive and Gram-negative divide should be nuanced. As the discovery of novel Ps-CLPs accelerates, current challenges to complete and maintain a useful overview of biological activity are discussed.